2015
DOI: 10.2105/ajph.2015.302668
|View full text |Cite
|
Sign up to set email alerts
|

Reports of Insurance-Based Discrimination in Health Care and Its Association With Access to Care

Abstract: Further research and policy interventions are needed to address insurance-based discrimination in health care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 35 publications
6
49
0
Order By: Relevance
“…It is unknown if a lack of sufficient Spanish language services, turnover of providers at safety-net healthcare facilities, overbooked appointment schedules, or patients not requesting appointments with a specific provider were the causes. Perceived discrimination, both insurance-based and due to being Hispanic, was described, similar to findings of other studies with Hispanics in various regions of the U.S. (Calo et al, 2015; Han, Call, Pintor, Alarcon-Espinoza, & Simon, 2015; Keller et al, 2010; Reininger et al, 2014). Persons without insurance or having publically supported health insurance have reported greater difficulty getting a timely appointment and higher odds of forgoing needed care as compared to those with private insurance (Han et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…It is unknown if a lack of sufficient Spanish language services, turnover of providers at safety-net healthcare facilities, overbooked appointment schedules, or patients not requesting appointments with a specific provider were the causes. Perceived discrimination, both insurance-based and due to being Hispanic, was described, similar to findings of other studies with Hispanics in various regions of the U.S. (Calo et al, 2015; Han, Call, Pintor, Alarcon-Espinoza, & Simon, 2015; Keller et al, 2010; Reininger et al, 2014). Persons without insurance or having publically supported health insurance have reported greater difficulty getting a timely appointment and higher odds of forgoing needed care as compared to those with private insurance (Han et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Similar studies report a relationship between discrimination and unmet health needs 15,17 where the number of experiences with discrimination is positively associated with a greater odds of delay in seeking medical care. 27 Some contrary studies have found that experiences with discrimination are not independently predictive of preventive healthcare utilization.…”
Section: Discussionmentioning
confidence: 63%
“…1013 In 2013, the average rate of Medicaid acceptance was 45.7% in the U.S’s largest 15 cities. 14 Medicaid beneficiaries often report experiences of discrimination based on their insurance 15,16 including provider-patient interactions that felt demeaning. 17 Importantly, people who report experiencing this form of insurance-based discrimination are less likely to receive preventive health services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some health care institutions and providers refuse to give care based on health insurance status and type of insurance. 30 Also, Jacobs et al 26 examined AA perceptions of providers and found that many AAs believed providers were only after profit and were interested in experimentation during routine care visits. Some AAs additionally mentioned hearing about or witness- We also investigated the extent to which sex, SES, and insurance status moderated the relationship between perceived discrimination and provider trust and satisfaction.…”
Section: Discussionmentioning
confidence: 99%